Turkey between NATO and Russia: The failed balance. Turkey's S-400 purchase and implications for Turkish relations with NATO - Mehmet Yegin (Stiftung Wissenschaft und Politik (SWP), 2019)
Turkey's purchase of a Russian S-400 air defense missile system has raised questions concerning Turkey's alliance with the North Atlantic Treaty Organization (NATO) and the country's future intentions. Nonetheless, a break with NATO is unlikely, as alliance dependence is still applicable for both Turkey and other members. Turkish government circles have cast the recent purchase as a means to gain more autonomy from and/or better bargaining power with Western allies. However, the purchase of S‑400s will not bring about the desired outcomes. Instead, it will generate a dual dependency characterized by vulnerability to Russia and an increased need for assurances from NATO. Turkey also seems to have reached the limits of its bargaining power, as the United States is placing more weight on punitive measures. The only explanation left for the purchase is the possibility that President Tayyip Erdoğan may be seeking a domestic rally effect via a confrontation with the United States to prevent possible challengers to his leadership from gaining momentum.
Keywords: 320